How much is enough in rehabilitation? High running workloads following lower limb muscle injury delay return to play but protect against subsequent injury - Stares, J.; Dawson, B.; Peeling, P.; Drew, M.; Heasman, J.; Rogalski, B.; Colby, M. (Journal of Science and Medicine in Sport, 2018)
Objectives: Examine the influence of rehabilitation training loads on return to play (RTP) time and subsequent injury in elite Australian footballers. Design: Prospective cohort study. Methods: Internal (sessional rating of perceived exertion: sRPE) and external (distance, sprint distance) workload and lower limb non-contact muscle injury data was collected from 58 players over 5 seasons. Rehabilitation periods were analysed for running workloads and time spent in 3 rehabilitation stages (1: off-legs training, 2: non-football running, 3: group football training) was calculated. Multi-level survival analyses with random effects accounting for player and season were performed. Hazard ratios (HR) and 95% confidence intervals (CI) for each variable were produced for RTP time and time to subsequent injury. Results: Of 85 lower limb muscle injuries, 70 were rehabilitated to RTP, with 30 cases of subsequent injury recorded (recurrence rate = 11.8%, new site injury rate = 31.4%). Completion of high rehabilitation workloads delayed RTP (distance:>49,775 m [reference: 34,613-49,775 m]: HR 0.12, 95%CI 0.04-0.36, sRPE:>1266 AU [reference: 852-1266 AU]: HR 0.09, 95%CI 0.03-0.32). Return to running within 4 days increased subsequent injury risk (3-4 days [reference: 5-6 days]: HR 25.88, 95%CI 2.06-324.4). Attaining moderate-high sprint distance (427-710 m) was protective against subsequent injury (154-426 m: [reference: 427-710 m]: HR 37.41, 95%CI 2.70-518.64). Conclusions: Training load monitoring can inform player rehabilitation programs. Higher rehabilitation training loads delayed RTP; however, moderate-high sprint running loads can protect against subsequent injury. Shared-decision making regarding RTP should include accumulated training loads and consider the trade-off between expedited RTP and lower subsequent injury risk. ABSTRACT FROM AUTHOR